The Pragmatics of Paratextual Apparatus of Contemporary Latvian and American Travelogues - Ozola, Diāna (Respectus Philologicus, 2023)
The present research aims at investigating the pragmatic features of paratext and their functions in contemporary American and Latvian travelogues. The presence of numerous paratextual elements in travel writing often helps to differentiate the genre among other literary genres. This, together with the fact that Latvian travelogues are not frequently studied, adds novelty to the present research. In addition, paratextual apparatus plays an essential role in constructing the modality of a travel narrative; moreover, certain paratextual elements (photographs, illustrations, archival documents, etc.) serve as a witness for the veracity and authenticity of narration as well as create a communicative bond with a potential reader. Paratextual apparatus can be viewed from various perspectives due to the fact that its elements bear various functions from informative (preface, postscript, genre specification, etc.) to performative (dedication, epigraph, etc.). The research focuses on such paratextual elements as extended titles, genre specification, dedications, epigraphs, illustrative and archival materials used in several Latvian and American travelogues of 1962–2015. The research methodology was based on the analytical and cultural historical methods, which contributed to the deeper insight into the concept of paratextuality. The pragmatics of paratext in travel writing was investigated by means of synthesising the structural-semiotic method and the method of comparative analysis in the critical perception of travelogues under consideration.
Keywords: travel writing; travelogue; pragmatics; paratext; peritextual and epitextual elements